Needs Analysis for Blended Learning Models and Project-Based Learning to Increase Student Creativity and Productivity in Writing Scientific Papers - Santi Oktarina; Sri Indrawati; Adeng Slamet (AL-ISHLAH: Jurnal Pendidikan, 2023)
The era of the COVID-19 pandemic is the gateway to the famous online learning system. With the rapid development of educational technology and the familiarity of lecturers and students with this system, this method will become permanent in the future. By utilizing diverse learning mediums, blended learning will be a possibility. However, not all instructors are capable of designing courses in this manner. One of them is studying scientific paper writing. Since it was able to optimize this learning based on scientific studies, the project-based learning model was chosen to be paired with blended learning. To get a learning model that suits your needs requires a needs analysis. The purpose of this research was to gather information about students' needs to design blended learning models mixed with project-based learning to boost student creativity and productivity in writing. Scientific papers at the Indonesian Language Education Study Program. A survey method was used in this investigation. A questionnaire was utilized to obtain the data. The sample for this study was collected on purpose. There were 172 students in the research sample. The data analysis methodologies employed were qualitative and quantitative. The study's findings indicate that students require blended learning and project-based learning structures.